E-MODULE DEVELOPMENT BASED FLIP BOOK MAKER FOR CHARACTER BUILDING IN PANCASILA COURSEWORK SRIWIJAYA UNIVERSITY - Asmi, Adhitya Rol; Dhita Surbakti, Aulia Novemy; C., Hudaidah (Universitas Pendidikan Indonesia, 2018)
E-module is one of educational technology developments that can improve the quality of the teaching process. This study aims to develop an e-module based application Flip Book Maker in the Pancasila Education coursework. Research method using Borg and Gall development model. This research is divided into three stages: (a) needs assessment; (b) development of Flip Book Maker based e-module on Character Education chapter; and (3) trial and effectiveness test of Flip Book Maker based e-module on Character Education chapter. The results showed that the Flip Book Maker based e-module on Character Education chapter in Pancasila Education coursework is effective for strengthening student character and also effective in improving learning outcomes.